Integrating organic chemical simulation module into SWAT model with application for PAHs simulation in Athabasca oil sands region, Western Canada. (January 2019) - Du, Xinzhong; Shrestha, Narayan Kumar; Wang, Juyne
Abstract: An integrated watershed model is a key tool for assessing the fate and transport of organic chemicals. We developed and integrated an organic chemical simulation module into Soil Water Assessment Tool (SWAT) model and used it for Polycyclic Aromatic Hydrocarbons (PAHs) simulation in Muskeg River Watershed in Athabasca oil sands region, Western Canada. The model uses a three-phase partition process to simulate the chemicals partitioning to Dissolved Organic Carbon (DOC) in both soil water and streams. The simulation performances for Phenanthrene and Pyrene loads for a period of 2015–2017 were assessed to be of 'satisfactory' quality. The model simulation results indicated that the summer season is the hot moment and the rainfall-runoff event is the driving force for the PAHs transport in the watershed. The developed simulation module could be a useful modeling tool to simulate and asess the pathway, fate and transport of organic chemicals at the watershed scale. Graphical abstract: Image 1 Highlights: An organic chemical simulation module including terrestrial and aquatic processes was integrated into SWAT model. Three phases chemical partitioning process was incorporated based on soil and stream DOC simulations. Watershed-scale modeling of organic chemical was performed in Athabasca oil sands region for the first time. The integrated model is capable of assessing the fate, transport and pathways of organic chemical at watershed-scale.